Impact of Role Demands on Work-Life Balance: A Study of Executive Level Employees in Apparel Industry, Sri Lanka - Kaushalya, K.D.P.; Welmilla, I. (Department of of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka., 2020)
This study was done to assess the relationship and impact of role demands (work demand and family demand) on work-life balance by mediating the role of inter role conflicts in executive-level employees in the apparel industry, Sri Lanka. The study was an explanatory quantitative study conducted as a cross-sectional field study that applied a hypothetical deductive approach. The convenience sampling method was used to select sample units, and an online-based questionnaire (google form) was used to collect data. The analysis was done by using descriptive statistics, correlation, and linear regression analysis. Results revealed that work demand is significantly related to inter role conflicts, which impacts work-life balance. Similarly, family demands also significantly related to inter-role conflicts, which has an impact on work-life balance. Further, inter role conflicts is found to be a full mediator for both relationships. It concluded that work demand and family demand create inter-role conflicts, which hinders executive-level employees' work-life balance in the apparel industry, Sri Lanka.
Keywords: Family Demand, Inter Role Conflicts, Work Demand, Work-Life Balance